2008
DOI: 10.1001/archdermatol.2007.58
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality and Patient Satisfaction in Dermatology Office Practice

Abstract: M any dermatologists are under pressure to improve the efficiency and effectiveness of their clinical care in an era of stagnant reimbursement and higher office expenses. In addition, dermatologists in the United States are under increased scrutiny from payers, regulators, and patients who expect uniformly high-quality service from their physicians. The presence of increasing numbers of nondermatologist health care providers marketing themselves as skincare specialists also places increased pressure on dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…This implied that satisfied patients are more likely to pay higher cost for counselling service should it be charged. This finding is in line with studies conducted in USA . The median and average cost reported in our study was PKR 200, that is, US $ 1.73 and PKR 346, that is, US $ 3.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This implied that satisfied patients are more likely to pay higher cost for counselling service should it be charged. This finding is in line with studies conducted in USA . The median and average cost reported in our study was PKR 200, that is, US $ 1.73 and PKR 346, that is, US $ 3.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, studies have estimated a loss of US dollar ($) two hundred thousand as lifetime income of the practice attributed to patient loss due to dissatisfaction . From a legal perspective, increased patient satisfaction decreases the chance of malpractice suits …”
Section: Introductionmentioning
confidence: 99%
“…Selected patient satisfaction survey results, including those of the Consumer Assessment of Healthcare Providers and Systems (CAHPS) surveys, are available to the public and can influence patients' decisions on where to seek care. Satisfied patients are also less likely to file malpractice claims 16,17 . By addressing patient satisfaction, practices and institutions can increase market share, patient retention, referrals, and, ultimately, revenue 16,18 .…”
Section: Why It Matters: the Implications Of Patient Satisfactionmentioning
confidence: 99%
“…9 As a primarily outpatient-based specialty with high volume, dermatology may be well informed from the study of these online perspectives. Previous qualitative studies [10][11][12][13][14][15] have identified general factors associated with high patient satisfaction within medicine. These factors include care access, physician demeanor, quality of medical care processes, continuity of care, quality of health care facilities, and office staff characteristics.…”
mentioning
confidence: 99%